Macroeconomic factors affecting unemployment rate in Malaysia / Muhammad Iman Nurhakim Nazaruddin - Nazaruddin, Muhammad Iman Nurhakim (2022)
As early as the first decade of the twentieth century, unemployment was identified as a severe problem worldwide. This research aims to find out how all the macroeconomic factors, which are economic growth rate, inflation rate, foreign direct investment rate, and the population growth rate, affect the unemployment rate in Malaysia. The sample will be in Malaysia, and each variable will have 30 objectives from 1991-to 2020. The research method will be quantitative as we will take the data from secondary data platforms such as MacroTrend, International Labour Organization, Eikon Datastream, and other certified sources allowed. Based on the findings of this research, I found that two variables are significant towards Unemployment Rate: economic growth rate and foreign direct investment rate. The other two variables, the inflation rate, and the population growth rate, are not significant. This research will bring major implications to the government, investors, and policymakers. Furthermore, I also relate this research with some popular economic theories: Okun's Law and the Phillips Curve. Lastly, I can conclude that the variables affect the unemployment rate in Malaysia directly or indirectly.